\(x-\dfrac{12}{8\cdot11}-\dfrac{12}{11\cdot14}-\dfrac{12}{14\cdot17}-...-\dfrac{12}{32\cdot35}=\dfrac{43}{70}\) (phải là `32*35` chứ nhỉ?)
\(x-\left(\dfrac{12}{8\cdot11}+\dfrac{12}{11\cdot14}+\dfrac{12}{14\cdot17}+...+\dfrac{12}{32\cdot35}\right)=\dfrac{43}{70}\)
\(x-4\left(\dfrac{3}{8\cdot11}+\dfrac{3}{11\cdot14}+\dfrac{3}{14\cdot17}+...+\dfrac{3}{32\cdot35}\right)=\dfrac{43}{70}\)
\(x-4\left(\dfrac{1}{8}-\dfrac{1}{11}+\dfrac{1}{11}-\dfrac{1}{14}+\dfrac{1}{14}-\dfrac{1}{17}+...+\dfrac{1}{32}-\dfrac{1}{35}\right)=\dfrac{43}{70}\)
\(x-4\left(\dfrac{1}{8}-\dfrac{1}{35}\right)=\dfrac{43}{70}\\ x-4\cdot\dfrac{27}{280}=\dfrac{43}{70}\)
\(x-\dfrac{27}{70}=\dfrac{43}{70}\\ x=\dfrac{43}{70}+\dfrac{27}{70}\\ x=\dfrac{70}{70}=1\)
=>\(x-4\left(\dfrac{3}{8\cdot11}+\dfrac{3}{11\cdot14}+...+\dfrac{3}{32\cdot35}\right)=\dfrac{43}{70}\)
=>\(x-4\left(\dfrac{1}{8}-\dfrac{1}{11}+\dfrac{1}{11}-\dfrac{1}{14}+...+\dfrac{1}{32}-\dfrac{1}{35}\right)=\dfrac{43}{70}\)
=>\(x=\dfrac{43}{70}+4\cdot\dfrac{27}{280}=\dfrac{43}{70}+\dfrac{27}{70}=1\)